Cultural competency and nursing care among sundanese nurses ethnic group in Indonesia - Upit Pitriani; Kusman Ibrahim; Sandra Pebrianti (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Nurses as one of the health professionals who are expecting to have competence in providing nursing care to patients based on cultural background.Purpose: To describe the cultural competency and nursing care among sundanese nurses' ethnic group in Indonesia..Method: A descriptive design with a quantitative approach. The sampling technique in this study used Cluster Random Sampling with the sample of 63 respondents. The instrument used the NCCS (Nurse Cultural Competence Scale). This research conducted on April 2019 at dr. Slamet Hospital, Garut - IndonesiaResults: Shows that the nurses' cultural competencies in dr. Slamet hospital was in a low category of 37 respondents (58.7%). While in a component, cultural awareness was in the low category (60.3%), the cultural knowledge component was in the high category (52.4%), the cultural sensitivity component was in the low category (58.7%) and the cultural skills component in the high category (58.7%).Conclusion: The most nurses' cultural competencies  was in a low category such as cultural awareness was in the low category (60.3%), the cultural sensitivity component was in the low category. Sundanese nurses' ethnic group need to develop training in culturally competent as a local wisdom.